**Answer:**

y = ( x-4)(x+7)

**Step-by-step explanation:**

When we know the zeros of the equation, we can write the equation in the form

y= a(x-z1) (x-z2) where a is a constant and z1 and z2 are the zeros (solutions)

y = a( x-4)(x--7)

y =a( x-4)(x+7)

Since its says write an equation, we can pick a and I will let a=1

y = ( x-4)(x+7)

**Statement**: If p, then q

**Inverse**: If q, then p

**Converse**: If not p, then not q

**Contrapositive**: If not q, then not p.

We can see from the statement that p = brush teeth twice a day and q = not get cavities.

Thus:

**Inverse**: If I don't get cavities, then I brush my teeth twice a day. FALSE (for example, I might floss extra well instead. Brushing my teeth twice a day is not the only way to avoid cavities)

**Converse: **If I don't brush my teeth twice a day, then I get cavities. FALSE (for example, I might not eat a lot of sugar and thus I don't get cavities)

**Contrapositive**: If I get cavities, then I did not brush my teeth twice a day. TRUE

If this confuses you, try the example of p = cat and q = four legs. (i.e. the statement is If this is a cat, it has four legs). Try making the inverse, converse, and contrapositive, and see the truth of those statements.

You can conclude from this experiment that Alan's new medication is effective in reducing coughing from the the results of the treatment group.

Answer:

13.5 hours

Step-by-step explanation:

If it takes Amy 12 hours to complete the job alone

And it takes Tom 15 hours to complete the same job alone,

How long will it take for both of them to get the job done together?

Amy= 12 hours

Tom= 15 hours

Amy + John =?

(12 + 15)/ 2

27/2= 13.5 hours.

So it would take Amy and Tom 13.5 hours to complete the job together.